Improving Student Reading Literacy through the Reading Corner Program at MI Salafiyah 2 Tasikmadu - Ahmad Hinanda Nuriyanto; Putri Wijayanti; Zeti Aprilia Nurafni (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This study examines efforts to improve students’ reading literacy through the implementation of a classroom reading corner program at MI Salafiyah 2 Tasikmadu. The main problem addressed is the low level of reading interest and comprehension among elementary students, which affects their academic development and learning engagement. The research applies a classroom action research approach conducted in two cycles involving planning, implementation, observation, and reflection. Data were collected through observation, reading comprehension tests, interviews, and documentation to capture behavioral and cognitive changes in students. The findings indicate that the reading corner program successfully fostered a supportive literacy environment, increased voluntary reading participation, and significantly improved students’ comprehension skills. Students demonstrated greater confidence in retelling texts and showed consistent reading habits. The study concludes that a structured reading corner program can serve as an effective and sustainable literacy strategy in elementary schools. The model is practical, low-cost, and adaptable, offering important implications for strengthening school literacy culture and guiding future literacy development programs.